Development and Validation of a Parent Version of the Social, Academic, and Emotional Behavior Risk Screener in an Elementary Sample. (August 2019) - Taylor, Crystal N.; Allen, Amanda; Kilgus, Stephen P.; von der Embse, Nathaniel P.; Garbacz, Andrew S.
A line of research has supported the incremental and construct validity of multi-informant assessment. Accordingly, multiple universal screening systems have been designed to support the collection of information from multiple informants. The purpose of the study was to expand the Social, Academic, and Emotional Behavior Risk Screener (SAEBRS) suite of tools to include a novel parent form (SAEBRS-P). Specific aims of the study included the examination of SAEBRS-P factor structure, internal consistency reliability, and concurrent validity. Screening was conducted across four elementary schools in the Pacific Northwest with 212 students and their parents. Factor analytic results supported the retention of four factors, which demonstrated acceptable internal consistency reliability. Further analyses supported SAEBRS-P concurrent criterion-related validity, indicating moderate to high correlations between SAEBRS-P and Strengths and Difficulties Questionnaire (SDQ) scales. Limitations and implications for research are discussed.